2020
DOI: 10.33899/ijvs.2019.125738.1144
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological and neurobehavioral effects of chlorpyrifos and deltamethrin insecticides in mice

Abstract: The aim of the present study was to determine the acute toxicity of chlorpyrifos and deltamethrin in mice separately and to study their toxic and neurobehavioral effects. Median Lethal Doses (LD50) of chlorpyrifos and deltamethrin were determined depending on up and down method. The oral LD50 of chlorpyrifos was 193.05 mg/kg and of deltamethrin was 15.71 mg/kg in mice. The oral administration of chlorpyrifos 155 mg/kg and deltamethrin 12.56 mg/kg represent 80% of LD50 resulted in acute signs of poisoning that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Interestingly, the current work results identified that cinnamaldehyde improved the activity of deltamethrin against the larvae employed for this work. Cinnamomum osmophloeum leaf essential oil was found to act as a larvicide against Anopheles gambiae s.s larvae (17,25), and these co-workers predicted that this activity might have been due to cinnamaldehyde (26). The current work used cinnamaldehyde with deltamethrin to synergize the activity of each other resulting in high rates of mortalities in these larvae.…”
Section: Discussionmentioning
confidence: 86%
“…Interestingly, the current work results identified that cinnamaldehyde improved the activity of deltamethrin against the larvae employed for this work. Cinnamomum osmophloeum leaf essential oil was found to act as a larvicide against Anopheles gambiae s.s larvae (17,25), and these co-workers predicted that this activity might have been due to cinnamaldehyde (26). The current work used cinnamaldehyde with deltamethrin to synergize the activity of each other resulting in high rates of mortalities in these larvae.…”
Section: Discussionmentioning
confidence: 86%
“…Twenty-four male albino rats 170-200 gram weight were housed in the animal house under the steady status of temperature 24±2°C for three weeks prior to the beginning of the experiment, the animal house under laboratory conditions 12/12 hours light -dark cycle (20,21) and being preserved on a standard water and diet ad libitium (22,23). The animals were treated according to the specific guidelines of the veterinary medicine faculty and the study was approved by the Animal Ethics Committee of the University of Kufa.…”
Section: Experimental Animal Designmentioning
confidence: 99%
“…Medicine, University of Tikrit. Rats underwent to standard laboratory conditions (9), and free to access to food and water during the experimental period of 14 days. Rats distributed into four groups: Control group administrated with distilled water 1 ml/kg orally using tubular gavage, second group administrated with Ciprofloxacin 750 mg/kg orally, and third group administrated with a solution of Arabic gum solution 15% orally and fourth group administrated with both Ciprofloxacin 750 mg/kg and Arabic gum solution 15%.…”
Section: Preparation Of Experimental Subjectsmentioning
confidence: 99%
“…blood centrifuged at 3000 rpm for 15 minutes to obtain the serum. Serum kept in a deep freeze -80ºC until biochemical tests performed (9,10).…”
Section: Blood Sample Preparationmentioning
confidence: 99%